Intersection of Artificial Intelligence (AI) in Entertainment Sector - Nautiyal, Radhika; Jha, Radhey Shyam; Kathuria, Samta; Chanti, Yerrolla; Rathor, Navjot; Gupta, Manish (2023 4th International Conference on Smart Electronics and Communication (ICOSEC), 2023)
The media and entertainment sector are one of the most significant global industries and one of the first to adopt cutting-edge technological advancements. With the development in Artificial Intelligence (AI) technology, the entertainment sector has seen considerable changes in recent years. AI has revolutionized how people enjoy entertainment by upending conventional methods of content generation, distribution, and consumption. In order to emphasis the role, prospects, and limitations of AI in influencing the future of entertainment, this research study aims to examine the intersection between AI and the entertainment sector. This research study examines the current as well as potential consequences of AI in several entertainment industry sectors, including cinema, music, gaming, even virtual reality, through a comprehensive study of existing literature & industry examples. The study further addresses the social and ethical consequences of AI in the entertainment industry, including issues with bias, privacy, and copyright. The conclusion of this research study includes a perspective on AI's potential applications in the entertainment sector.